2021
DOI: 10.5194/acp-21-14761-2021
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and diurnal variations in biogenic volatile organic compounds in highland and lowland ecosystems in southern Kenya

Abstract: Abstract. The East African lowland and highland areas consist of water-limited and humid ecosystems. The magnitude and seasonality of biogenic volatile organic compounds (BVOCs) emissions and concentrations from these functionally contrasting ecosystems are limited due to a scarcity of direct observations. We measured mixing ratios of BVOCs from two contrasting ecosystems, humid highlands with agroforestry and dry lowlands with bushland, grassland, and agriculture mosaics, during both the rainy and dry seasons… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 88 publications
0
2
0
Order By: Relevance
“…The standard conditions were selected due to the key factors controlling plant and microbial production, respectively (Guenther et al, 1995;Tang et al, 2019). EFs for crop BVOC are currently applying the same standard conditions as that used for tree species (Guenther et al, 2012), and lots of studies on crop EFs were calculated by inversing the MEGAN model on an ecosystem or an individual plant scale (Bachy et al, 2016;Gonzaga-Gomez et al, 2019;Liu et al, 2021a). We summarized the crop EFs from published articles and presented the values in Table 5.…”
Section: Challenges In Setting Emission Factorsmentioning
confidence: 99%
“…The standard conditions were selected due to the key factors controlling plant and microbial production, respectively (Guenther et al, 1995;Tang et al, 2019). EFs for crop BVOC are currently applying the same standard conditions as that used for tree species (Guenther et al, 2012), and lots of studies on crop EFs were calculated by inversing the MEGAN model on an ecosystem or an individual plant scale (Bachy et al, 2016;Gonzaga-Gomez et al, 2019;Liu et al, 2021a). We summarized the crop EFs from published articles and presented the values in Table 5.…”
Section: Challenges In Setting Emission Factorsmentioning
confidence: 99%
“…MEGAN (Model of Emissions of Gases and Aerosols from Nature) inventory quantifies net biogenic emissions of isoprene and other gases emitted by vegetation into the atmosphere (Guenther et al, 2006;Sindelarova et al, 2014). Isoprene, α-pinene and β-pinene, which account for the largest proportion of BVOCs emitted by vegetation in Africa (Ferreira et al, 2010;Jaars et al 2016;Liu et al, 2021;Saxton et al, 2007;Serça et al, 2001), were identified and used in this study. A more detailed description of these emission inventories is discussed in the work of García-Lázaro et al ( 2018), Guenther et al (2006) and Vitolo et al (2018).…”
Section: Nox and Voc Emissionsmentioning
confidence: 99%